KARAKTERISTIK KLINIKOPATOLOGI PSORIASIS DI RSUP PROF. DR. I G. N. G. NGOERAH DENPASAR PERIODE TAHUN 2011-2021 - -, Jerry; Saputra, Herman; Ekawati, Ni Putu; Sumadi, I Wayan Juli (E-Jurnal Medika Udayana, 2024)
Psoriasis is a skin disease that can affect all ages. Many people think that skin diseases do not endanger human life, but psoriasis can be complicated into a more serious disease. This study aims to determine the clinicopathological characteristics of psoriasis at Prof. Dr. I G. N. G. Ngoerah Central Hospital Denpasar in 2011-2021. This study used a cross-sectional design with total sampling from secondary data at the Anatomical Pathology Installation of Prof. Dr. I G. N. G. Ngoerah Denpasar. Of the 75 samples obtained, the most cases of psoriasis were psoriasis vulgaris (54.7%) which was dominated by male patients (70.7%), where most cases occurred in the age group of 31-40 years (24.0%). Most of the lesions were found locally, especially on the body area (54.7%). Of all medical record data that included family history (21.3%), all cases stated that there was no family history of psoriasis. Most of patients’ main complaints were red spots (57.3%). The majority of patients had a match between the clinical diagnosis and the clinicopathological diagnosis (73.3%). These findings can provide insight into the clinicopathological characteristics of psoriasis so that it can be detected as early as possible and given appropriate treatment. It is necessary to carry out further analytical research to look for the relationship between various variables.